Pengaruh Macam Inokulum Dan Lama Inkubasi Pupuk Organik Terhadap Pertumbuhan Dan Hasil Padi - Sarjiyah, Sarjiyah (Universitas Muhammadiyah Yogyakarta, 2014)
The experiment aimed to know the best inoculant and incubation time of organic fertilizer to the growth and yield of paddy. The experiment was conducted in Kasihan, Bantul, Yogyakarta. The altitude of experiment site is 110 m above sea level with the soil type of regosol.The experiment used the 3 x 4 factorial with one control and was arranged in Randomized Completely Block Design with three block as replication. The first factor was kind of inoculant to make organic fertilizer, consisted of 3 levels i.e (1) without inoculant, (2) EM4 and (3) Stardec. The second factor was incubation time, consisted of 4 levels i.e (1) 7 days, (2) 14 days, (3) 21 days and (4) 28 days. The control used organic fertilizer (Urea, SP36, KCl) with recommended dose.The result showed that neither organic fertilizer without inoculant nor with addition of EM4 and Stardec (with incubation time 7-28 days) affected significantly to the growth and yield of paddy, the used 3ton/hectare of organic fertilizer with or without inoculant did not affect significantly to the yield of paddy.